The Role of Trabectedin in Soft Tissue Sarcoma - Nakamura, Tomoki; Sudo, Akihiro (Frontiers in Pharmacology, 2022)
Background: Systemic chemotherapy for advanced disease is one of the therapeutic options for the management of metastases in soft tissue sarcomas (STS). Doxorubicin, used either alone or in combination with ifosfamide, has been used as a first-line chemotherapy. Furthermore, in the past decade, new drugs, such as trabectedin, pazopanib, and eribulin, have been shown to be effective in the treatment of advanced STS after the failure of first-line anthracycline-based chemotherapy. However, the appropriate usage of these drugs has not yet been established. Methods: In this review, we have summarized reports of clinical trials of trabectedin, focusing on the efficacy and toxicity of trabectedin in the treatment of STS. Results: Trabectedin can be administered safely and effectively to patients with advanced STS as a second-line or further treatment. Although trabectedin may be effective as a first-line treatment in selected patients, anthracycline-based chemotherapy should still be recommended as doxorubicin remains the gold standard first-line treatment for locally advanced or metastatic STS. Currently, no combination treatment with trabectedin matches the gold standard. Nucleotide excision repair (NER) and homologous recombination (HR) repair may contribute to the efficacy of trabectedin. Conclusions: In conclusion, trabectedin has a favorable toxicity profile and is a potential therapeutic alternative for patients with advanced STS.